Analysis of the Relationship between Nutritional Status and Health of Female Workers Who Received and Didn't Get Nutritious Food and Drinks on Night Work Shifts - Tresye Widiastuty Paidi; Evi Mulyaningsih (GoAcademica Research & Publishing, 2022)
The government presents special protection for woman workers who works at the night shift. Requiring employer to provide nutritious food and beverage according to Manpower Act also, it is regulated on Ministerial Decree No. 224 Year 2003, Labour inspectors found some companies were not comply the regulation, it has an impact towards nutrition status and health of woman night shift worker. The research design were used quantitative analysis with cross sectional design by using univariate and bivariate test. The activity was carried out on two companies that gave and did not provide nutritious food and drinks. Sampling was done by using purposive sampling with total sampling 95 respondents. Statistical tests showed that there was no significant relationship between the adequacy of energy, protein and fat with the provision of nutritious food and beverages in the night shift. There was a tendency of Fat Sufficiency Rate (AKL) on company which provided nutritious food and beverage higher than company which did not provide in a day. There was no difference proportion (unrelated) between provide food and beverage with BMI, anemia status, blood pressure, monthly pain for woman night shift worker and significant relations on age, marital status and working hours on BMI. Suggestion: 1). The Companies are advised to comply with the obligation to provide nutritious food and beverage for workers, adjust the number of calories according to the needs of workers and the type of work; 2). Workers are advised to exercise regularly; 3). The government should review the rules regarding the obligation to give 1400 calories and improve the quidance and supervision of Occupotional Safety and Health (OSH) norms, especially work nutrition.